2021
DOI: 10.1002/ecs2.3553
|View full text |Cite
|
Sign up to set email alerts
|

Incongruent long‐term trends of a marine consumer and primary producers in a habitat affected by nutrient pollution

Abstract: Incongruent long-term trends of a marine consumer and primary producers in a habitat affected by nutrient pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
1
6
1
Order By: Relevance
“…With green turtle populations growing and a key finding of this study being that smaller green turtles in the IRL were more likely to have FP, it might be expected that FP rates would increase over time as the size structure of the IRL shifts toward a higher proportion of small turtles. However, our data did not show an increase in FP rates over time, and notably there was no trend in size structure over time in the IRL during this study (Long et al, 2021).…”
Section: Fibropapillomatosis Disease Dynamicscontrasting
confidence: 87%
See 1 more Smart Citation
“…With green turtle populations growing and a key finding of this study being that smaller green turtles in the IRL were more likely to have FP, it might be expected that FP rates would increase over time as the size structure of the IRL shifts toward a higher proportion of small turtles. However, our data did not show an increase in FP rates over time, and notably there was no trend in size structure over time in the IRL during this study (Long et al, 2021).…”
Section: Fibropapillomatosis Disease Dynamicscontrasting
confidence: 87%
“…A short-term tracking study in the IRL showed most turtles had small home ranges at the IRL site (Redfoot & Ehrhart, 2008), but there are no long-term studies on site fidelity in the IRL. Relatively low recapture rates in the IRL (~8%; Long et al, 2021) bring site fidelity into question, but the study site is very small (~1 km 2 ) relative to the useable area of the IRL, which may lead to low recapture rates when considering the broader IRL system as a single foraging aggregation. Additionally, many turtles in this study were recaptured across long periods of time (average time between recaptures was about 1.9 years, with 25 turtles recaptured at least 5 years apart, UCFMTRG, unpublished data), implying some level of long-term site fidelity may exist.…”
Section: Potential For Differential Capture Probability To Affect Hie...mentioning
confidence: 99%
“…For the juvenile IRL and TRID mixed stocks, the mean SCL from individuals sampled in our study was comparable to the mean sizes previously reported for both sites 37 , 59 . For the rookery MB, the mean size and observed reduction in mean SCL among nesting females are consistent with a trend recently described for this populations 60 .…”
Section: Discussionsupporting
confidence: 89%
“…in open oceanic habitats for the first years of their life (Reich et al 2007;Witherington et al 2012;Mansfield et al 2021). When they reach a minimum size of 20-25 cm straight-line standard carapace length (nuchal notch-posterior tip) hereafter referred to as SSCL, green turtles undergo ontogenetic diet and habitat shifts (Price et al 2017) and begin feeding primarily on drift macroalgae and seagrass species found in neritic waters (Holloway-Adkins 2001;Redfoot and Ehrhart 2013;Long et al 2021). These "smaller juvenile" green turtles (Small Juveniles) can be found in nearly all nearshore waters around the state of Florida as they grow to maturity (Ehrhart et al 2007;Hart and Fujisaki 2010;Stadler et al 2015;Long et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ceriani et al (2015) demonstrated this with the loggerhead turtle (Caretta caretta) rookery located on the Atlantic coast of Florida and their associated foraging grounds. While this relationship has yet to be established for green turtles, Long et al (2021) found that small juvenile green turtles in the Indian River Lagoon of Florida have been dropping in abundance despite the decade plus increase in green turtle nesting numbers nearby (Chaloupka et al 2008). While small juvenile foraging aggregations in the Indian River Lagoon of Florida likely comprise turtles from multiple rookeries and management units (Bass and Witzell 2000), these distinctions have yet to be parsed out, the trends are nevertheless concerning.…”
Section: Introductionmentioning
confidence: 99%